2012
DOI: 10.1177/073989131200900210
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Model for E-Mentoring Christian Education Students

Abstract: This article describes an exploratory study of synchronous and asynchronous mentoring of Christian education students at Dallas Baptist University. In recent years, as the practice of faculty mentoring students has emerged, the role of a mentor has been expanded beyond face-to-face mentoring to include e-mentoring. An e-mentoring program in Christian education should focus on rich and engaging course content, Christ-centered integration, campus community, and a personal connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies can be found on mentoring dating back to the 1980s (Educause, n.d.) and even further during the days of Moses and Joshua in (Mullen, 2012). "While there are differences in the way mentoring has been defined in these research studies, the overall findings are fairly consistent over the span of years" (Educause, n.d.).…”
Section: Introductionmentioning
confidence: 86%
“…Studies can be found on mentoring dating back to the 1980s (Educause, n.d.) and even further during the days of Moses and Joshua in (Mullen, 2012). "While there are differences in the way mentoring has been defined in these research studies, the overall findings are fairly consistent over the span of years" (Educause, n.d.).…”
Section: Introductionmentioning
confidence: 86%